The art of keeping time - Quigley, Paula (My University, 2020)
Like the protagonist, both the short story and the short film are subject to the demand to arrive ‘on time’. Violently freed from the imperatives of conventional storytelling, this film considers the moment when the laws of time and language fall away in favour of an eternal ‘they is’.
PUBLISHED
Keywords: Henri Bergson; ‘duration'; ‘mathematical time’; short film; short story; film memory